Praktik Fotografi sebagai Media Mengenal Warna (Sebuah Penelitian Eksperimen Pada Anak Usia Dini) - nilda syah, naziah (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2025)
The media plays an important role in distributing information and supporting the learning process, especially for early childhood. To increase the effectiveness of learning, the use of the right methods, such as photography practices, can help children recognize colors in a fun way. This method not only encourages cognitive development, but also improves children's memory, creativity, and understanding. With an approach that combines learning and play, it is hoped that children can more easily absorb material, optimize intellectual potential, and present a more memorable learning experience. The results of observations on two children showed progress in recognizing colors after practicing photography. Child I and Child II initially faced difficulties, especially in mentioning the color of objects. However, as time went by, Child I managed to recognize that the leaves were green, while Child II showed increased comfort when photographing objects. Photography activities carried out in colorful environments facilitate the exploration and learning of colors effectively. In conclusion, photography media has been proven to be effective in improving color recognition skills in early childhood.